Titles of books popularizing knowledge about the Polish language published in the 21st century. Structural, semantic and pragmatic analysis - Cieśla, Bartłomiej; Sokół-Klein, Anna (Papers in Linguistics, 2024)
The aim of the article is to perform a structural, semantic and pragmatic analysis of book titles popularizing knowledge about the Polish language. The titles come primarily from 21st-century publications of the following types: linguistic and rhetorical guides, feuilletons, essays, books presenting theoretical findings regarding phenomena present in the Polish language, as well as publications falling into the category of extended interviews. 90 proper names varying in terms of meaning, structure and functionality were considered. The analysis of the collected units was preceded by a short description of such problems as the popularization of knowledge about language and the status of titles in the light of previous onomastic research. The conducted study proved that the analysed ideonyms show a high level of heterogeneity at the syntactic and semantic level. Not only do they contain a summarizing component, but also exhibit such thematic segments as information about the genological status of the publication, metalinguistic commentary, apparent dialogicity, etc. Moreover, the names constitute a form of persuasive influence on recipients by using, for example, semantic vagueness, appeal, evaluation, questions, or creating a community of the sender and their recipients.